2017
DOI: 10.1371/journal.pone.0184318
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of innate immune activation by clinical isolates of respiratory syncytial virus

Abstract: Respiratory syncytial virus (RSV) is a major respiratory pathogen of infants and young children. Multiple strains of both subgroup A and B viruses circulate during each seasonal epidemic. Genetic heterogeneity among RSV genomes, in large part due to the error prone RNA-dependent, RNA polymerase, could mediate variations in pathogenicity. We evaluated clinical strains of RSV for their ability to induce the innate immune response. Subgroup B viruses were used to infect human pulmonary epithelial cells (A549) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 77 publications
2
33
0
Order By: Relevance
“…The most abundant mRNA they observed was associated with the G gene [40]. Levitz et al reported the G gene to be the most highly expressed gene at later time-points in A549 cells infected with isolates from the RSV/B subgroup [43]. Thus, recent published data indicate that patterns of RSV gene expression vary and do not always follow a gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant mRNA they observed was associated with the G gene [40]. Levitz et al reported the G gene to be the most highly expressed gene at later time-points in A549 cells infected with isolates from the RSV/B subgroup [43]. Thus, recent published data indicate that patterns of RSV gene expression vary and do not always follow a gradient.…”
Section: Discussionmentioning
confidence: 99%
“…By homology with other NNS viruses, it is widely assumed that transcription in RSV follows a gradient, where the extent to which a gene is transcribed falls with its distance from the 3’ promoter [29, 39, 40]. Earlier studies reported data consistent with a gradient [39, 41, 42]; however, recent studies show mRNA abundances that peak at the G gene, which is located in the middle of the genome [40, 43]. We recently reported the G gene to be the most abundant in clinical samples obtained from RSV/A- and RSV/B-infected infants [44].…”
Section: Introductionmentioning
confidence: 99%
“…This is believed to be due to transcriptional attenuation at the intergenic (IG) regions, although the mechanisms underlying the attenuation are unknown [34]. Earlier studies reported results consistent with a gradient [32,35,36]; however, recent studies show RSV mRNA abundances that peak at the G gene, which is the seventh gene downstream of the 3' promoter of the genome [33,37]. We recently reported the G gene to be the most abundant in clinical samples obtained from RSV/A-and RSV/B-infected infants [38].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is a common viral infection, there is still no efficient therapy. The hurdles in obtaining an efficient therapy reside in several issues: the immaturity of the immune system of infants and young children, the different virulence potential of clinical strains that trigger a different cytokine/chemokine response and the involvement of multiple molecular, still unknown pathways (Levitz et al, 2017). The identification of antiviral immune mechanisms and a comprehensive characterization of virus-specific immune responses, using new cellular and animal models would help to define new aspects of the viral -host crosstalk that would modulate the severity of infection.…”
Section: Resultsmentioning
confidence: 99%